<h2>
Answer:</h2>
<em><u>Recursive equation for the pattern followed is given by,</u></em>
![a_{n}=a_{n-1}+(n-1)^{2}](https://tex.z-dn.net/?f=a_%7Bn%7D%3Da_%7Bn-1%7D%2B%28n-1%29%5E%7B2%7D)
<h2>
Step-by-step explanation:</h2>
In the question,
The number of interaction for 1 child = 0
Number of interactions for 2 children = 1
Number of interactions for 3 children = 5
Number of interaction for 4 children = 14
So,
We need to find out the pattern for the recursive equation for the given conditions.
So,
We see that,
![a_{1}=0\\a_{2}=1\\a_{3}=5\\a_{4}=14\\](https://tex.z-dn.net/?f=a_%7B1%7D%3D0%5C%5Ca_%7B2%7D%3D1%5C%5Ca_%7B3%7D%3D5%5C%5Ca_%7B4%7D%3D14%5C%5C)
Therefore, on checking, we observe that,
![a_{n}=a_{n-1}+(n-1)^{2}](https://tex.z-dn.net/?f=a_%7Bn%7D%3Da_%7Bn-1%7D%2B%28n-1%29%5E%7B2%7D)
On checking the equation at the given values of 'n' of, 1, 2, 3 and 4.
<u>At, </u>
<u>n = 1</u>
![a_{n}=a_{n-1}+(n-1)^{2}\\a_{1}=a_{1-1}+(1-1)^{2}\\a_{1}=0+0=0\\a_{1}=0](https://tex.z-dn.net/?f=a_%7Bn%7D%3Da_%7Bn-1%7D%2B%28n-1%29%5E%7B2%7D%5C%5Ca_%7B1%7D%3Da_%7B1-1%7D%2B%281-1%29%5E%7B2%7D%5C%5Ca_%7B1%7D%3D0%2B0%3D0%5C%5Ca_%7B1%7D%3D0)
which is true.
<u>At, </u>
<u>n = 2</u>
![a_{n}=a_{n-1}+(n-1)^{2}\\a_{2}=a_{2-1}+(2-1)^{2}\\a_{2}=a_{1}+1\\a_{2}=1](https://tex.z-dn.net/?f=a_%7Bn%7D%3Da_%7Bn-1%7D%2B%28n-1%29%5E%7B2%7D%5C%5Ca_%7B2%7D%3Da_%7B2-1%7D%2B%282-1%29%5E%7B2%7D%5C%5Ca_%7B2%7D%3Da_%7B1%7D%2B1%5C%5Ca_%7B2%7D%3D1)
Which is also true.
<u>At, </u>
<u>n = 3</u>
![a_{n}=a_{n-1}+(n-1)^{2}\\a_{3}=a_{3-1}+(3-1)^{2}\\a_{3}=a_{2}+4\\a_{3}=5](https://tex.z-dn.net/?f=a_%7Bn%7D%3Da_%7Bn-1%7D%2B%28n-1%29%5E%7B2%7D%5C%5Ca_%7B3%7D%3Da_%7B3-1%7D%2B%283-1%29%5E%7B2%7D%5C%5Ca_%7B3%7D%3Da_%7B2%7D%2B4%5C%5Ca_%7B3%7D%3D5)
Which is true.
<u>At, </u>
<u>n = 4</u>
![a_{n}=a_{n-1}+(n-1)^{2}\\a_{4}=a_{4-1}+(4-1)^{2}\\a_{4}=a_{3}+9\\a_{4}=14](https://tex.z-dn.net/?f=a_%7Bn%7D%3Da_%7Bn-1%7D%2B%28n-1%29%5E%7B2%7D%5C%5Ca_%7B4%7D%3Da_%7B4-1%7D%2B%284-1%29%5E%7B2%7D%5C%5Ca_%7B4%7D%3Da_%7B3%7D%2B9%5C%5Ca_%7B4%7D%3D14)
This is also true at the given value of 'n'.
<em><u>Therefore, the recursive equation for the pattern followed is given by,</u></em>
![a_{n}=a_{n-1}+(n-1)^{2}](https://tex.z-dn.net/?f=a_%7Bn%7D%3Da_%7Bn-1%7D%2B%28n-1%29%5E%7B2%7D)
Answer:
see explanation
Step-by-step explanation:
Under a rotation about the origin of 90°
a point (x, y ) → (- y, x ), thus
A(2, 2 ) → A'(- 2, 2 )
B(2, 4 ) → B'(- 4, 2 )
C(4, 6 ) → C'(- 6, 4 )
D(6, 4 ) → D'(- 4, 6 )
E(6, 2 ) → E'(- 2, 6 )
Answer:
![y = 2.cos(x) - 2](https://tex.z-dn.net/?f=y%20%3D%202.cos%28x%29%20-%202)
Step-by-step explanation:
1. Shifting
right or left, top or down, as the graph in the question has the same illustration of
. Consider
![y = a.cos(x) + b](https://tex.z-dn.net/?f=y%20%3D%20a.cos%28x%29%20%2B%20b)
2. find a and b by using two sample points from the graph:
and ![(\pi, -4)](https://tex.z-dn.net/?f=%28%5Cpi%2C%20-4%29)
![0 = a.cos(0) + b => a + b = 0\\ -4 = a.cos(\pi) + b => b-a=-4\\\left \{ {{2b=-4} \atop {2a=4}} \right.\\a = 2, b=-2\\](https://tex.z-dn.net/?f=0%20%3D%20a.cos%280%29%20%2B%20b%20%20%3D%3E%20a%20%2B%20b%20%3D%200%5C%5C%20-4%20%3D%20a.cos%28%5Cpi%29%20%2B%20b%20%3D%3E%20b-a%3D-4%5C%5C%5Cleft%20%5C%7B%20%7B%7B2b%3D-4%7D%20%5Catop%20%7B2a%3D4%7D%7D%20%5Cright.%5C%5Ca%20%3D%202%2C%20b%3D-2%5C%5C)
Answer:
here you go..............
Answer:
jssisvshdvdbd sjjsjdgdjd
Step-by-step explanation:
ususueuwgeieyevekeuecrjie r